Psoriasis vulgaris leaves a dynamic imprint on circulating and skin γδ TCR repertoires shaped by disease severity, age, and sex - Jirouš Drulak, Maja; Mihalj, Martina; Štefanić, Mario; Plužarić, Vera; Šola, Marija; Tolušić-Levak, Maja; Marković, Marina; Balogh, Peter; Tokić, Stana (Frontiers in Immunology, 2025)
Psoriasis vulgaris (PV) is a common, T cell mediated dermatosis with substantial systemic footprint. While αβ T cells are well established drivers of PV, the role of γδ T cells, including their abundance, clonal architecture and transcriptional programs in PV remain incompletely understood. To address this, we performed an integrated analysis of circulating and cutaneous γδ cells from 65 patients with PV and 35 healthy controls using TCR repertoire sequencing, bulk transcriptomics, and flow cytometry. In PV, disease severity and age drove contraction of peripheral γδ T cell repertoires, marked by loss of rare clonotypes and hyperexpansion patterns. Subset composition, segment usage, and CDR3 length of both skin and blood clonotypes were further modulated by age, disease severity, and sex, highlighting nuanced repertoire remodeling. TCRγ clonotypes showed partial overlap between blood and skin, whereas TCRδ clonotypes remained private and tissue-specific, with no PV-specific clonotypes identified. Transcriptomic profiling indicated that circulating γδ T cells adopt an activated, cytotoxic, tissue-homing phenotype, consistent with enhanced potential to migrate into and act within lesional skin, especially in a subset of patients. Collectively, these findings demonstrate that PV drives dynamic, clinically modulated remodeling of γδ T cells across compartments, positioning them as dynamic elements of the psoriatic immune landscape and potential targets for future functional and therapeutic investigation.